Brain Drug Delivery System: A Novel Review (Asian Journal of Pharmaceutics (AJP), 2024)
In the living world, 1.5 billion of people have been suffering from either one or another brain disease. The mostprobably causing diseases/disorders related to the function of the brain were autoimmune encephalitis, autoimmuneepilepsy, Hashimoto’s encephalopathy, Alzheimer’s disease (AD), and Wilson’s disease. As the brain’s extracellularmatrix contributes to the poorly distributed delivery of locally administered medications and the blood-brainbarrier functions as an impenetrable barrier for systemically injected treatments, drug targeting in the brain isone of the most difficult problems in pharmaceutical research. General strategies that can enhance medicationdelivery to the brain are very desirable for the treatment of several disorders affecting the central nervous system(CNS). When medications are given close to their optimal sites of action, they are both less hazardous and moreeffective. Several methods or novel approaches have been developed through various investigations to target thedrug to reach the affected area in the brain. The BBB is the most hurdles for the active ingredients to exhibit itsfunction so numerous approaches such as Nanoparticles, Lipoplexes, Scaffolds, Dendrimers, Polyanhydride, andReceptor-mediated transport (RMT) have been developed for improving drug action.